Wafer dicing vibration investigation on novel wafer mounting techniques - Mohd Noh, Mohd Syahrin Amri; Omar, Ghazali; Mispan, Mohd Syafiq; Harun, Fuaida; Othman, Md Nazri; Ngatiman, Nor Azazi; Mat Ibrahim, Masrullizam (Institute Of Electrical And Electronics Engineers Inc., 2024)
Chipping has emerged as a significant issue in semiconductor manufacturing, particularly during the dicing process. The existing conventional single-sided wafer mounting technique does not have sufficient holding capability which contributes to instability during dicing and causes higher chipping performance. The objective of the study is to develop a novel wafer mounting technique that can hold the wafer firmly during dicing and improve the chipping performance. In the experiment, chipping and vibration performance during the dicing process on novel double-sided semi and full-sandwich wafer mounting were investigated and compared with the conventional singlesided wafer mounting technique. Chipping was measured using high power scope and ImageJ software while the vibration was initiated using the NI 9234 Sound-Vibration Module and SDT1-028K Piezoelectric film. Implementing extended surface tape coverage on double-sided UV mounting tape for the full sandwich wafer mounting technique resulted in superior wafer gripping during dicing and produced the lowest topside and backside wafer chipping performance. The novel double-sided full sandwich wafer mounting technique has demonstrated higher wafer holding capability, resulting in lower vibration during dicing and improved overall chipping performance.